Designing for the post-pandemic era: Trends, focuses, and strategies learned from architectural competitions based on a text analysis - Han, Pei; Wang, Lingju; Song, Yufei; Zheng, Xi (Frontiers in Public Health, 2022)
The COVID-19 pandemic has made the built environment an important source of prevention and control, architects and scholars have thus been seeking countermeasures since the beginning of the outbreak. As design and construction cycles are long, few completed cases or evidence-based studies are available for reference. On the other hand, massive architectural competition works have emerged which always been the soil for discussion and practice of cutting-edge design issues. These contain a vast number of ideas for solutions from the perspective of urban and architectural design and even facilities and policies, which are valuable materials for analysis and research. Therefore, the exploration of competitions will provide us with public health intervention directions, strategies and a rethinking of the built environment. Using a text-mining approach, we analyzed 558 winning entries in architectural competitions related to the pandemic response, exploring specific issues, populations involved, coping strategies, and trends that emerged as the pandemic evolved. Our results show that the strategies proposed can be grouped into 17 keywords, with modularization being the most frequent strategy. Further, we explored the competition topics, focuses, and strategies directed against the pandemic and the value tendency of the competition within and outside China, which will provide a strategy reference for the design response to the pandemic, as well as help understand the influence and significance of social factors behind the divergence of issue focuses and strategic tendency in different regions and times.